2017
DOI: 10.1111/ibi.12540
|View full text |Cite
|
Sign up to set email alerts
|

Male feeding contribution facilitates multiple brooding in a biparental songbird

Abstract: Despite the cost of lost mating opportunities, biparental care is routinely observed across different groups of animals. Theory predicts that paternal care will increase reproductive success, yet many empirical studies have failed to find a direct link. Most studies have focused on the effect of paternal care on current breeding attempts, but male contributions may benefit future reproduction. Species producing clutches or litters more than once per season (i.e. multiple breeding attempts per season) are suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Similarly, Patterson et al (2011) suggested male tree swallows could compensate for decreased provisioning of their mates, although no male compensation for reduced maternal performance has also been found ( Hogle and Burness, 2014 ). Given the importance of male provisioning to nestling mass gain ( Lendvai and Chastel, 2010 ; Madliger and Love, 2016b ; Nomi, 2018 ), male nest box visits and paternal quality need to be considered when predicting a pairs' reproductive investment in a nest. Future studies should include male CORT levels, and their relationship with male feeding rates and reproductive success, as in Ouyang et al (2011a , b) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Patterson et al (2011) suggested male tree swallows could compensate for decreased provisioning of their mates, although no male compensation for reduced maternal performance has also been found ( Hogle and Burness, 2014 ). Given the importance of male provisioning to nestling mass gain ( Lendvai and Chastel, 2010 ; Madliger and Love, 2016b ; Nomi, 2018 ), male nest box visits and paternal quality need to be considered when predicting a pairs' reproductive investment in a nest. Future studies should include male CORT levels, and their relationship with male feeding rates and reproductive success, as in Ouyang et al (2011a , b) .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the level of parental care provided by male White-eyed Vireos is that such care reduces investment in parental care by their mates and, by doing so, increases the likelihood of females re-nesting if nests are predated or initiating second nesting attempts if initial attempts are successful (load-lightening hypothesis 24 ). For example, Nomi et al 25 found a positive correlation between the proportion of total provisioning visits made by male Japanese Tits ( Parus minor ) and the probability that their mates would have multiple broods. Males provisioning nestlings at higher rates may also improve nestling condition 25,26 and the likelihood of young surviving during the post-fledging period.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nomi et al 25 found a positive correlation between the proportion of total provisioning visits made by male Japanese Tits ( Parus minor ) and the probability that their mates would have multiple broods. Males provisioning nestlings at higher rates may also improve nestling condition 25,26 and the likelihood of young surviving during the post-fledging period.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies examined role of male parents on reproductive success, surprisingly few studies have evaluated paternal effects on the initiation of multiple breeding. Recently, Nomi et al (2017b) demonstrated that male feeding contribution strongly affects the probability of multiple breeding. The present study indicates another mechanism enhancing female multiple breeding by mediating breeding timing.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because the females are assumed to control the initiation of the second breeding. Since most passerine birds are socially monogamous with biparental care, male quality can also be an important factor for female parents to initiate a second breeding (Nomi et al 2017b). The most influential factor of FMB reported so far is the timing of breeding; early breeders are more likely to produce second clutches because the length of the breeding season is limited (Hoffmann et al 2015 and references therein).…”
Section: Introductionmentioning
confidence: 99%